2019
DOI: 10.3390/atmos10120753
|View full text |Cite
|
Sign up to set email alerts
|

Economic Valuation of Public Meteorological Information Services—A Case Study of Agricultural Producers in Taiwan

Abstract: Most meteorological information services in Taiwan are currently provided by the Central Weather Bureau, Ministry of Transportation and Communications. As agricultural production activities are sensitive to weather and climate conditions, meteorological information services are more important for agricultural decision-makers than those in other sectors. This study uses the contingent valuation method to estimate the economic value of meteorological information services in Taiwan for agricultural producers. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Economic barriers are also among the main obstacles for farmers to use meteorological information. The importance of this recommendation has been approved by other researchers see [33,54]. Lin et al [33] showed that the economic factors such as high cost of the meteorological information have a significant impact on the reluctance of farmers to use the weather prediction services in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic barriers are also among the main obstacles for farmers to use meteorological information. The importance of this recommendation has been approved by other researchers see [33,54]. Lin et al [33] showed that the economic factors such as high cost of the meteorological information have a significant impact on the reluctance of farmers to use the weather prediction services in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis on the use of incompatible technologies, lack of credit, social communication, low technical knowledge, habit, and lack of access to meteorological information Vietnam [28] Lack of proper access to information, low accuracy of predictions, and incomprehensible information Africa [29] Lack of access to information, cost of meteorological information, emphasis on old cultivation methods Zimbabwe [30] Lack of interaction between farmers and organizations, lack of access to information, low literacy, and infrastructural barriers Nigeria [31] Lack of access to information, demographic characteristics, cultural/normative problems, and infrastructural and political barriers Kenya [32] Problems with access to appropriate information, demographic characteristics, high cost of access to information, technical problems, and educational problems Taiwan [33] Lack of access to appropriate information and lack of training Myanmar [34,35] Hansen [36] argues that meteorological information must meet farmers' needs and be consistent with their decision-making goals. However, research studies show that a large proportion of farmers do not use meteorological information and weather forecasts in their decisions [35].…”
Section: Barriers Country/scale Of the Study Researchersmentioning
confidence: 99%
“…Although the KMA increased the TAF price, the production cost match collection ratio was still 12.1% in 2018. The low payback rate might trigger future attempts by the KMA to realize appropriate information Sustainability 2021, 13, 6965 2 of 13 charges. Understanding the private sector is essential to improve the government's policy performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers ask closed-or open-ended questions about users' recognition of the existence and accuracy of information, when or how information is utilized, and how much they are willing to pay for improving the information. The data collected from the respondents are proposed policies that can either improve the value of weather information or be utilized as base data for non-market valuation methods, such as the conjoint valuation method (CVM) [8][9][10][11][12][13]. Empirical research is performed to analyze the value of the general public or overall weather information, while the analytical approach considers specific situations wherein costs and losses occur depending on the users' decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Lin et al [7] estimate the economic value of meteorological information services for Taiwanese farmers from a study over 400 registered farmers in 20 municipalities. They use a contingent valuation method.…”
mentioning
confidence: 99%